2011
DOI: 10.1111/j.1651-2227.2011.02358.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial exchange transfusion results in increased cerebral oxygenation and faster peripheral microcirculation in newborns with polycythemia

Abstract: Partial exchange transfusion improves microcirculation in polycythemic newborns. Cerebral oxygenation increases and cFTOE decreases suggesting increased blood flow. Microvascular flow increases possibly representing reactive hyperperfusion after hemodilution. Whether these effects are beneficial require further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 28 publications
0
20
0
2
Order By: Relevance
“…It is well known that neonates who were exposed to fetal chronic hypoxia can present with polycythaemia,2 3 26 and it could, thus, be argued that the higher oxygen carrying capacity may confound our results. However, as high haematocrit appears to actually reduce CBF in preterm neonates due to higher blood viscosity,27 and treatment of polycythaemia by partial exchange transfusion restores CBF,28 it is unlikely that our findings could solely be explained by higher haematocrit levels in our SGA population.…”
Section: Discussionmentioning
confidence: 70%
“…It is well known that neonates who were exposed to fetal chronic hypoxia can present with polycythaemia,2 3 26 and it could, thus, be argued that the higher oxygen carrying capacity may confound our results. However, as high haematocrit appears to actually reduce CBF in preterm neonates due to higher blood viscosity,27 and treatment of polycythaemia by partial exchange transfusion restores CBF,28 it is unlikely that our findings could solely be explained by higher haematocrit levels in our SGA population.…”
Section: Discussionmentioning
confidence: 70%
“…Studies have shown that blood flow and microcirculation improved after partial blood exchange using Doppler ultrasonography and "near infrared" spectroscopy (14,15). However, some studies suggested that partial blood exchange did not contribute to neurological improvement in the neonatal period or in the long-term in symptomatic or asymptomatic infants (4)(5)(6)(7)16,17).…”
Section: Discussionmentioning
confidence: 99%
“…All 41 studies performed peripheral muscle NIRS measurements in human neonates. Twenty-one studies were identified to use peripheral muscle NIRS measurements as a single method [1,3,6,7,8,9,10,11,12,13,14,15,16,17,18,19,23,24,25,27,28] (table 1), 17 studies combined cerebral and peripheral muscle NIRS measurements [20,21,22,29,30,31,32,33,34,35,36,37,38,39,40,41,42] (table 2) and 1 study used multi-site NIRS measurements [43] (table 2) in human neonates. Two randomized studies were identified [12,36].…”
Section: Resultsmentioning
confidence: 99%
“…These measurements were also used as a monitor for cerebral and lower body tissue oxygenation during cardiopulmonary bypass operations with a blood-sparing approach [32] and during deep hypothermic circulatory arrest with regional low-flow perfusion [29]. In a clinical observational study simultaneous cerebral and peripheral NIRS measurements were also used to investigate the treatment effects of partial exchange transfusions in newborns with polycythaemia [34]. Partial exchange transfusions led to an increase in cerebral oxygenation, whereas peripheral oxygenation remained unchanged.…”
Section: Discussionmentioning
confidence: 99%